ANALISIS STRUKTUR CERITA PANJI DALAM PERTUNJUKAN DRAMA TARI WAYANG TOPENG MALANG LAKON PANJI RENI - Fitrotul Hikmah (JURNAL PUSAKA, 2016)
This study examines the puppet mask dance drama with the play Panji Reni Malang. This study focuses on the literary aspect relation to the Panji stories Reni terms of story structure. The Analysis of Panji story structure includes a series of plot, characters, themes, as well as sociological aspects. Exposition and instabilitasjuga as the beginning of the conflict appeared on the scene Janggala. Travelling flow switch on tahapkomplikasi and climax, this happens on a rural scene. The most recent series of plots that denoument, and occurs in rural scene until the scene Balinese kingdom. The characters in this drama are dominated by Raden Panji Asmara Bangun and Dewi Anggraeni. Another figures are Raden Panji Amiluhur (King Jenggala), Raja Panji Jayeng Tilam, Gadhing-Layaran-Pamecut and King Klana Jayeng Tilam. Another characters are Patih Kudapati, King Klana Maduretna, Patih Sabrang, Patih Bali and Bali soldiers. Daughter figures consist of Goddess Tejaswara (Queen Jenggala) and Dewi Anggraini. Supporting roles are Semar, Bagong, and demons. Sociological aspects of the story is influenced by the notion that people outside Java has a very violent temper, with no discretion. Background asa part forming Reni Panji stories can be performed in their entirety include Jenggala Kingdom scenes, scenes of forests, mountains or countryside scenes, scenes of Sebrang kingdom, and the Kingdom of Bali scene. Keywords: Panji Reni, drama, topeng, scenes.